Exploring The Mind of Gen Z: Deciphering E-wallet Adoption Through The Lens of TPB Theory - Berlianawati, Desi Intan; Nurabiah, Nurabiah; Ridhawati, Rini (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 19 No 1 (2024), 2024)
This study examines the factors contributing to the increasing compound annual growth of e-wallets in Indonesia, particularly within Generation Z. E-wallets are favored for transactions due to their perceived ease of use, enhanced security, and time-saving features. Additionally, the attractiveness of e-wallets is enhanced by promotions, discounts, and accessible account openings. This research adopts a quantitative approach, employing Partial Least Square (PLS) software to test hypotheses using the Structural Equation Model (SEM). A sample of 823 Generation Z individuals from various regions of Indonesia was analyzed. The findings indicate that attitudes towards behavior, subjective norms, perceived behavioral control, usage intentions, and actual behavior significantly influence Generation Z’s utilization of e-wallets. The study reveals that Generation Z frequently engages in daily transaction activities using e-wallets, predominantly influenced by the safety and convenience perceived in e-wallet technologies. Despite this reliance, it is noted that Generation Z often overlooks potential risks associated with e-wallet transactions, feeling secure with e-wallets as their primary transaction tool. This research enhances the understanding of e-wallet usage dynamics among Generation Z, emphasizing the significant impact of psychological and behavioral factors on the adoption of digital financial technologies. Keywords: determinants, e-wallet, generation Z, TPB